Caricom - alive and vigorous - Hoyte, Hugh Desmond (Office of the President GeorgetownGY, 1987)
Reports on the deliberations and decisions of the Eight Meeting of the Conference of Heads of Government of the Caribbean Community held in St Lucia from June 30th to July 3rd 1987.